Parental Expectation from Children with Cochlear Implants in Indian Context: a Questionnaire Based Study - Kumar,Prawin (2017)
Abstract Introduction Parental support is important in the habilitation/rehabilitation of children using cochlear implant devices. Hence, it is important for families to know the realistic expectations regarding outcomes from CIs. Objective The objective of the present study is to know the parents’ expectation from children using CIs. Methods For this study, we recruited 23 parents of children using CIs. We administered 15 questions translated in to Hindi related to communication abilities, social skills, academic achievement, change in future life, rehabilitation demand, and stress due to hearing impairment. Results The response of the questions (5-point rating scale) related to communication abilities showed that parents were expecting children using CIs to use the telephone (95%), to be able to detect soft sounds (99%), to listen in crowds (86%), to be able to easily understand others (76%), and to show improvement in communication skills (78%). Similarly, for questions related to social skills showed 90% of the parents expecting that their children with CIs should be able to easily make friends with normal hearing peers, and 80% of the parents were expecting the children to achieve high standards in their reading and writing skills. Questions related to change in future life showed 86% of the parents expecting their children with CIs to act like normal hearing children. Further, 78% parents showed positive response regarding importance of intensive training. However, 70% of the parents reported stress in the family due to the existence of the hearing impaired child. Conclusion Overall, the existing questionnaire-based study showed that parents have high expectations from their children with cochlear implant.